Self-Triggered MPC Design for Distributed Systems Subject to Global Coupled Constraints - Chen, Qianqian; Li, Shaoyuan (Chinese Control Conference, 2025)
This paper investigates a self-triggered distributed model predictive control (DMPC) approach for linear systems with external disturbances and global coupled constraints in communication-limited environments. To handle external disturbances, a robust constraint is imposed on the local system state, and the global coupled constraint is accordingly tightened. Based on this, an optimal control problem (OCP) and a self-triggered mechanism are designed to regulate the system's state and decrease computational overhead, respectively. At each predetermined triggered instant, the OCP is solved via a consensusbased algorithm, followed by the re-calculation of the open-loop phase. Sufficient conditions guaranteeing recursive feasibility and closed-loop stability are presented. Simulation results illustrate the validity of the proposed algorithm.